Atypical Neuroleptic Malignant Syndrome: Diagnosis and Proposal for an Expanded Treatment Algorithm. Issue 12 (15th December 2017) - Schreiner, Nicole M.; Windham, Samuel; Barker, Andrew
Abstract : Neuroleptic malignant syndrome (NMS) in the absence of an elevated creatine kinase is atypical and more difficult to diagnose. We present a patient with NMS significant risk factors who developed atypical NMS 6 days after a liver transplant. Symptoms of hyperthermia, altered mental status, dyskinesia, and autonomic instability (hypertension and tachycardia) coincided with promethazine administration, with rapid progression to fulminant NMS with lead pipe rigidity after a single injection of intramuscular ziprasidone. Rapid diagnosis and management resulted in full patient recovery. Differential diagnoses for NMS are discussed and a treatment algorithm is proposed.